Pemahaman Etika Berdagang Pada Pedagang Muslim Pasar Wonokromo Surabaya (Studi Kasus Pedagang Buah) - Siti Nur Azizaturrohmah; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Trading is a job that is highly recommended in Islam, because the Prophet and the companions also a traders. So it should as a good Muslim in performing daily activities in accordance with the guidance of the Prophet in order to be successful the world and the hereafter included in trade. Ethics of trade was good manners and behavior in the trade so the customers were satisfied.This study aims to determine the understanding of ethical trade in the Muslim traders Wonokromo Market Surabaya. This study used a qualitative approach with descriptive case study method. Determination of informants using purposive sampling technique. Data collected by means of semi-structured interviews and documentation. Data analysis using descriptive analytical model.The results of this study indicate that generally Muslim traders Wonokromo Markets have understood the ethical trade based on the principle of unity, equilibrium, free will, responsibility and truth in a way that is honest and good trade (do not cheat), provide information to the customer in accordance with reality, appropriately weigh, not hold a fake offers, do not tucking rotten fruit into a nice fruit, and helping others among fellow traders nor traders with collector. REFERENCESAfifudin, Beni dan Ahmad Saebani. 2009. Metodologi Penelitian Kualitatif. Pustaka SetiaAl-Utsaimin, Syaikh Muhammad bin Salih. 2007. Syarah Riyadus Shalihin, jilid 3. Terjemahan Ali Nur. Jakarta Timur: Darus Sunnah Press.Alwasilah, A. Chaedar. 2002. Pokoknya Kualitatif. Jakarta: PT. Dunia Pustaka Jaya.Beekun, Rafiq Issa. 1997. Islamic Business Ethict, Virginia: International Institute of Islamic Thought.Departemen Pendidikan dan Kebudayaan. 1996. Kamus Besar Bahasa Indonesia Edisi Kedua. Jakarta: Balai Pustaka.Fuad,M.dkk. 2006. Pengantar Bisnis. Jakarta: PT Gramedia Pustaka Utama.Jusmaliani, M.E.dkk. 2008. Bisnis Berbasis Syariah. Jakarta: Bumi Aksara.Majalah Al-Hikmah. http://majalah.pengusahamuslim.co m/pemasaran-dalam-perspek tifislam/ jam 7.28 12 april 2013.Moleong, Lexy J. 2002. Metode Penelitian Kualitatif. Bandung. PT. Remaja Rosdakarya.Muhamad dan Lukman Fauroni. 2003. Visi Al-Qur’an Tentang Etika dan Bisnis. Jakarta: Salemba Diniyah.Muhammad, Irsyad. 2012. Etika Bisnis Dalam Perspektif Islam. Semarang: Pustaka AmaniMunawwir, Ahmad Warson. 1984. Kamus Al-Munawwir. Yogyakarta: PP. Krapyak.Naqvi, Syed Nawab. 1993, Ethict and Economics: An Islamic Syntesis, diterjemahkan oleh Husin Anis: Etika dan Ilmu Ekonomi Suatu Sintesis Islami. Bandung: Mizan.Pusat Pengkajian dan Pengembangan Ekonomi Islam (P3EI). 2008. Ekonomi Islam. Jakarta: PT. Raja Grafindo Persada.Sugiyono. 2011. Metodologi Penelitian Kuantitatif Kualitatif dan R&D. Bandung: ALFABETA. Surabaya Post. http://www.surabayapagi.com/inde x.php?3b1ca0a43b79bdfd9f9305b8 12982962457c689935c0e9fab661496 55f5f7917Susanto, Ahmad. 2009. Fiqih Muamalah. Yogyakarta: Kanisius.Titus, Harold H. dkk. 1984. Persoalanpersoalan Filsafat. H.M. Rosyidi (terj), Jakarta: Bulan Bintang.Wiranata, I Gede A.B. 2012. Etika Bisnis&Hukum Bisnis (Sebuah Pemikiran Awal ). Bandar Lampung: Penerbit Universitas Lampung.Yin, Robert K. 2009. Case Study Research: Design and Methods. Edisi Keempat. United States of America: SAGE Publications, Inc.